A Study to find out the Efficacy of Strip Immunoassay Test for Insulin Like Growth Factor Binding Protein -1 in Amniotic Fluid for Detection of Premature Rupture of Membranes (Global Journal of Medical Research, 2023)
Background It is an obstetric conundrum which is poorly defined with an obscure etiology difficulty in diagnosis association with significant maternal and neonatal morbidity and mortality with diverse and controversial management strategies Aim and Objectives To know the efficacy of strip immunoassay test in amniotic fluid for detection of premature rupture of membranes Materials and Methods A hospital based observational study carried out on 60 pregnant women attending emergency and OPD with complaints of leaking per vaginum Strip immunoassay test was performed on all the participants along with a conventional method like ferning and the results obtained were analysed for calculating the diagnostic accuracy of the test
Keywords: premature rupture of membranes; ferning; strip immunoassay test; insulin like growth factor binding protein-1